2019
DOI: 10.1097/pas.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Uterine Sarcomas Represent Under-Recognized High-grade Endometrial Stromal Sarcomas

Abstract: Undifferentiated uterine sarcoma is a diagnosis of exclusion with limited molecular genetic data available. Recent recognition of high-grade endometrial stromal sarcomas with diverse genotypes suggests that some tumors classified as undifferentiated uterine sarcomas may represent misdiagnosed high-grade endometrial stromal sarcomas. Archival material from 10 tumors diagnosed as undifferentiated uterine sarcomas in 2009-2017 were collected. BCOR immunohistochemistry and fluorescence in situ hybridization (FISH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 20 publications
(25 reference statements)
6
72
0
1
Order By: Relevance
“…These findings suggest that LMS variants, recently described fusion‐driven sarcomas and other possibly distinctive clinicopathological entities with as‐yet undiscovered translocations probably contribute to the perceived morphological and genetic diversity of UUS. Similar observations were made in our separate study, which showed that 70% of UUS were in fact misdiagnosed HGESS harbouring YWHAE – NUTM2 , ZC3H7B–BCOR and BRD8‐PHF1 fusions as well as BCOR ITD by FISH and targeted RNA sequencing . These mutations were found among tumours showing uniform cytological atypia.…”
Section: Uussupporting
confidence: 88%
See 4 more Smart Citations
“…These findings suggest that LMS variants, recently described fusion‐driven sarcomas and other possibly distinctive clinicopathological entities with as‐yet undiscovered translocations probably contribute to the perceived morphological and genetic diversity of UUS. Similar observations were made in our separate study, which showed that 70% of UUS were in fact misdiagnosed HGESS harbouring YWHAE – NUTM2 , ZC3H7B–BCOR and BRD8‐PHF1 fusions as well as BCOR ITD by FISH and targeted RNA sequencing . These mutations were found among tumours showing uniform cytological atypia.…”
Section: Uussupporting
confidence: 88%
“…Absent BCOR staining favours ZC3H7B–BCOR fusion‐positive HGESS over the occasional purely spindled HGESS with BCOR ITD; however, suspected BCOR genetic abnormalities should be confirmed by molecular methods. Most tumours classified as UUS, at least for the subset composed of cells with uniform nuclear features, represent misdiagnosed HGESS with known genetic abnormalities and as such, UUS should be a diagnosis of exclusion . BCOR expression in ≥50% of tumour cells corresponds to the presence of BCOR fusion or ITD in almost 90% of previously diagnosed UUS …”
Section: High‐grade Endometrial Stromal Sarcoma With Bcor Genetic Abnmentioning
confidence: 99%
See 3 more Smart Citations